An effective method for measuring text legibility in XR devices reveals clear differences between three devices - Kilpeläinen, Markku; Häkkinen, Jukka (Frontiers in Virtual Reality, 2023)
Reading is a crucial aspect of the extended reality (XR) experience across various professional and recreational contexts. Legibility, which is defined as the ease with which a character can be recognized, is an essential determinant of readability. As legibility on a specific device cannot be deduced from technical specifications alone, an efficient perceptual method for measuring legibility is needed to measure the legibility of text presented in XR. In this study, we present a method for comparing the legibility limits of XR devices, where single letter legibility is measured with fast and precise psychophysical methods. We applied the method to compare the legibility in three commercial XR headsets (Varjo VR-2, HTC Vive Pro Eye, Oculus Quest 2) in experiments with human observers. Our results show that the single letter legibility methods presented here provide an effect size approximately ten times higher compared to the widely used method of reading speed. This allows for the use of fewer observers and the detection of smaller differences, making it a more efficient and effective approach for comparing the legibility limits of XR devices.